A PROSPECTIVE COMPARATIVE OBSERVATIONAL STUDY ON SAFETY, EFFICACY AND COST EFFECTIVENESS OF INSULIN AND THEIR ANALOGUES - Rodrigues, Prudence Attilade; Balan, Anu; Purushothaman, Charumathi (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: The objective of this study was to compare safety, efficacy and cost effectiveness of insulin and their analogues when compared with human insulin in patients with type-2 diabetes mellitus. Methods: A prospective observational study was carried out in a multispecialty hospital. The inpatients and outpatients from general medicine and endocrinology departments were included in our study for a period of 6 mo. The diabetic profile such as FBS, PPBS, HbA1c and body weight of the diabetic patients at the initial visit and follow up visit was documented. Results: This study showed a statistically significant reduction in HbA1c, PPBS, and FBS levels from the baseline in insulin analogue users. It was found that, insulin analogue with metformin showed statistical improvement (P<0.05) in FBS, PPBS, HbA1c as well as body weight and also found to be a cost-effective treatment according to Incremental cost-effectiveness ratio (ICER) decision matrix. Conclusion: This study concluded that type 2 diabetes patients underlined with the treatment using insulin analogue showed a better glycemic control when compared to human insulin. Metformin was the better OHA option in type-2 diabetes mellitus when compared with sulphonylureas and also metformin showed less weight gain than sulphonylureas.